Energy consumption, international trade, and real income in the USA: An empirical investigation using conditional error correction models - Katircioglu, Salih; Fethi, Sami; Kalmaz, Demet Beton; Caglar, Dilber; Taspinar, Nigar (Amer Inst Physics, 2014)
This study investigates the empirical relationship between energy consumption, international trade, and real income in the USA, which is the second largest energy consuming country following China. It employs bounds tests to level relationships and conditional error correction models through Auto-Regressive Distributed Lag specification. Using annual data from the 1960 to 2010 period, the results reveal a long-term relationship between energy consumption, international trade, and real income in the USA. It is also found that energy consumption is determinant of exports, imports, and real income. Conditional Granger causality tests suggest that there is a feedback relationship between energy consumption, international trade, and real income in the long-term for the USA economy. (C) 2014 AIP Publishing LLC.
Keywords: Economic-Growth; Co2 Emissions; Electricity Consumption; Causal Relationship; Granger Causality; Higher-Education; Tourism; Output; Panel; Hypothesis